The Influence of the Film "KKN Desa Penari" on Tourist Visit Interest in Film-Induced Tourism in Plunyon Kalikuning Destination, Sleman, Yogyakarta - Nufail Naisaburi, Muhammad; Khairune Nisa, An Nuur; Intan Nurmala Fadin, Delfyan (Jurnal Toursci, 2023)
Film-induced tourism has emerged as a dynamic facet of the contemporary tourism landscape, leveraging the visual and cultural appeal portrayed in films to enhance the attractiveness of destinations. This study delves into the impact of the Indonesian horror film "KKN di Desa Penari" on tourist visitation in the picturesque Plunyon, Kalikuning, Cangkringan, and Sleman regions of Yogyakarta. The research methodology involves an exploration of the nexus between the film's scenes and tourists' destination choices. The study gauges the impact by analyzing tourists' interest in film locations and their expectations regarding the benefits of engaging in film-induced tourism. The research uses a mixed-methods approach, encompassing surveys, interviews, and data analysis to discern patterns in tourist behavior and motivations influenced by the film. Understanding the interplay between cinematic representation and tourist decision-making is crucial for the tourism and film industries. The findings aim to contribute insights into the dynamics of film-induced tourism, providing valuable information for stakeholders to optimize the potential of cinematic representations in attracting and retaining tourists in the captivating landscapes showcased in "KKN di Desa Penari."